Adsorption-Based Removal of Sb (III) from Wastewater by Graphene Oxide-Modified Zirconium-Based Metal-Organic Framework Composites - Yilu Deng; Qiming Mao; Shuang Luo; Xiande Xie; Lin Luo (Adsorption Science & Technology)
The treatment of Sb (III) wastewater produced from mining activities is uniquely challenging and has therefore garnered increasing attention. Here, an amino-modified zirconium-based metal-organic framework material (UiO-66-NH2) and its composites were loaded onto graphene oxide (GO@UiO-66-NH2) via the hydrothermal method, after which these materials were used to adsorb Sb (III) in mine wastewater. The effects of adsorption time, pH, initial Sb (III) concentration, temperature, and adsorbent dosage on the removal performance of Sb (III) were then investigated. The adsorption processes of Sb (III) were examined via adsorption kinetic, isotherm, and thermodynamic analyses. XRD, SEM, and FTIR analyses demonstrated the presence of a porous structure and high levels of oxygen-containing functional groups on the UiO-66-NH2 and GO@UiO-66-NH2 surfaces. During the Sb (III) adsorption process, the adsorption rates of UiO-66-NH2 and GO@UiO-66-NH2 were very fast in the first 10 minutes, and the adsorption equilibrium was achieved in 12 h, with the adsorption efficiencies of 91.76% and 93.79%, respectively. At a pH of 7.0, 25°C, an initial Sb (III) concentration of 100 mg/L, and an adsorbent dosage of 0.04 g/L, the maximum Sb (III) adsorption capacities of UiO-66-NH2 and GO@UiO-66-NH2 reached 39.23 mg/g and 61.07 mg/g, respectively. The adsorption process was accurately described by the Langmuir model, meaning that the Sb (III) was adsorbed through single-layer uniform adsorption. Moreover, the adsorption process was highly consistent with the pseudo-second-order model, which was indicative of spontaneous and endothermic chemical adsorption. Additionally, the Sb (III) removal efficiency could be maintained approximately 70% after sorption-desorption recycling four times. Therefore, our study provides an economical and effective method for the removal of Sb (III) in wastewater treatment.